2021
DOI: 10.3917/cisl.2101.0053
|View full text |Cite
|
Sign up to set email alerts
|

Entend-on vraiment les paysans ? Ce que la variation syntaxique nous dit des représentations sociales dans la littérature des XV e et XVI e  siècles

Abstract: Les Cahiers internationaux de sociolinguistique 2 qu'indirectement et par le biais de l'écrit qui est arrivé jusqu'à nous (Ayres-Bennett 2004 : ix ; Martineau 2013 : 130). Les linguistes diachroniciens (depuis Marchello-Nizia 2012) ont montré l'intérêt des travaux portant sur l'oral représenté dans les textes pour l'étude de l'évolution du français et ont défini le cadre théorique et la méthodologie d'une telle approche. L'étude de Romaine de la variation syntaxique en moyen-écossais (1982) donne, quant à elle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In the future, in order to continue seeking for the embedded Wh-in situ clause, we will pursuit the exploration of oral and written corpora established in contexts of communicative proximity, and take a closer look at introductory verbs, particularly weak verbs (Blanche-Benveniste 1989;Blanche-Benveniste & Willems 2007, 2016, from a macro-syntactic perspective; moreover, the study of the extended contexts of each attestation observed here, in its complementarity with other embedded or nonembedded Wh-structures (standard, all the Wh-words:::), will offer a promising perspective. Finally, an exploration in historical sociolinguistics of old judicial corpora containing ordinary reported speech (Dourdy & Spacagno 2020;Dourdy 2021) should allow us to date the rise of direct and embedded in situ interrogatives more precisely, and possibly attest the existence of the Wh-in situ in embedded form as early as the seventeenth century.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, in order to continue seeking for the embedded Wh-in situ clause, we will pursuit the exploration of oral and written corpora established in contexts of communicative proximity, and take a closer look at introductory verbs, particularly weak verbs (Blanche-Benveniste 1989;Blanche-Benveniste & Willems 2007, 2016, from a macro-syntactic perspective; moreover, the study of the extended contexts of each attestation observed here, in its complementarity with other embedded or nonembedded Wh-structures (standard, all the Wh-words:::), will offer a promising perspective. Finally, an exploration in historical sociolinguistics of old judicial corpora containing ordinary reported speech (Dourdy & Spacagno 2020;Dourdy 2021) should allow us to date the rise of direct and embedded in situ interrogatives more precisely, and possibly attest the existence of the Wh-in situ in embedded form as early as the seventeenth century.…”
Section: Discussionmentioning
confidence: 99%